The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/jhc.s44380
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for hepatocellular carcinoma: an evidence-based review of its place in therapy

Abstract: Transarterial chemoembolization (TACE) is the standard treatment for patients with Barcelona Clinic Liver Cancer-intermediate stage hepatocellular carcinoma (HCC). The concept of drug-eluting bead TACE builds on the rationale of intratumoral drug delivery, and drug-eluting bead TACE has been shown to provide consistent and reliable results and to significantly diminish systemic drug exposure, liver toxicity, and drug-related adverse events as compared with conventional TACE. Based on the belief that combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This may be related to the activation of related signaling pathways after embolization and the induction of neoangiogenesis, forming a microenvironment conducive to tumor proliferation (25). In addition, the serum concentrations of vascular endothelial and fibroblast growth factors increase after TACE, and the serum levels are positively correlated with tumor progression (26). Tumor cells with low Ki67 expression are less sensitive to chemotherapeutic drugs, and the therapeutic effect of the drugs is less than the proliferation induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the activation of related signaling pathways after embolization and the induction of neoangiogenesis, forming a microenvironment conducive to tumor proliferation (25). In addition, the serum concentrations of vascular endothelial and fibroblast growth factors increase after TACE, and the serum levels are positively correlated with tumor progression (26). Tumor cells with low Ki67 expression are less sensitive to chemotherapeutic drugs, and the therapeutic effect of the drugs is less than the proliferation induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…These clinicians reported that the efficacy of mTACE in patients with HCC is better than that of conventional TACE. [ 109 111 ]…”
Section: Several Issues That Deserve Further Studymentioning
confidence: 99%
“…Transcatheter arterial chemoembolization (TACE) is a locoregional therapy that not only blocks the tumor blood supply through the use of an embolization agent but also infiltrates the tumor tissue resulting in a high concentration of the chemotherapeutic agent specifically within the tumor tissue. TACE is widely utilized to treat patients with unresectable liver cancer due to its favorable efficacy and tolerable side effects ( 4 ). Traditionally, the drug carriers in conventional TACE (cTACE) consist of lipiodol, a gelatin sponge, particles and other compounds, which fail to stably release chemotherapeutic agents and embolize target arteries accurately and completely ( 5 ).…”
Section: Introductionmentioning
confidence: 99%